2011
DOI: 10.1021/bi200596w
|View full text |Cite
|
Sign up to set email alerts
|

Deep-UV Resonance Raman Analysis of the Rhodobacter capsulatus Cytochrome bc1 Complex Reveals a Potential Marker for the Transmembrane Peptide Backbone

Abstract: Classical strategies for structure analysis of proteins interacting with a lipid phase typically correlate ensemble secondary structure content measurements with changes in the spectroscopic responses of localized aromatic residues or reporter molecules to map regional solvent environments. Deep-UV resonance Raman (DUVRR) spectroscopy probes the vibrational modes of the peptide backbone itself, is very sensitive to the ensemble secondary structures of a protein, and has been shown to be sensitive to the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 57 publications
2
29
0
1
Order By: Relevance
“…Aromatic amino acids are precursors for various biologically important molecules,s uch as neurotransmitters and hormones.B ys electively investigating these biomolecules,i t would be possible to directly address certain metabolic pathways.F urthermore,i tcan be postulated that the overall composition of these molecular species can be used to identify tissue conditions or cellular states.M ajor advantages of UV resonance Raman spectroscopy are also the absence of af luorescence background and the signal enhancement by the resonance effect, which improve the signal quality and lead to fast data acquisition times.E arly attempts to inves-tigate biological samples were reported in the late 1990s, when the first UVRR data of viruses were reported, along with assignments of the observed Raman bands at different UV excitation wavelengths. [157] Multiwavelength UVRR was employed to spectroscopically characterize different growth phases of bacteria. [155] Nucleotide distributions were observed with resonant bands attributable to guanine and adenine.I n2 004, Jarvis and Goodacre demonstrated the feasibility of UVRR for the discrimination of bacteria of the urinary tract.…”
Section: Uvrr To Probe Aromatic Amino Acids and Nucleobasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aromatic amino acids are precursors for various biologically important molecules,s uch as neurotransmitters and hormones.B ys electively investigating these biomolecules,i t would be possible to directly address certain metabolic pathways.F urthermore,i tcan be postulated that the overall composition of these molecular species can be used to identify tissue conditions or cellular states.M ajor advantages of UV resonance Raman spectroscopy are also the absence of af luorescence background and the signal enhancement by the resonance effect, which improve the signal quality and lead to fast data acquisition times.E arly attempts to inves-tigate biological samples were reported in the late 1990s, when the first UVRR data of viruses were reported, along with assignments of the observed Raman bands at different UV excitation wavelengths. [157] Multiwavelength UVRR was employed to spectroscopically characterize different growth phases of bacteria. [155] Nucleotide distributions were observed with resonant bands attributable to guanine and adenine.I n2 004, Jarvis and Goodacre demonstrated the feasibility of UVRR for the discrimination of bacteria of the urinary tract.…”
Section: Uvrr To Probe Aromatic Amino Acids and Nucleobasesmentioning
confidence: 99%
“…Deep-UVRR was used to study the interactions of the Rhodobacter capsulatus cytochrome bc1 complex, at ransmembrane protein that is sensitive to conformational changes. [157] Multiwavelength UVRR was employed to spectroscopically characterize different growth phases of bacteria. [158] However, compared to resonance Raman spectroscopy in the visible region, reports on cell and tissue samples are less frequent, probably owing to the susceptibility of biological samples to UV radiation.…”
Section: Uvrr To Probe Aromatic Amino Acids and Nucleobasesmentioning
confidence: 99%
“…34 A small number of other detergent-solubilized membrane proteins have also been investigated, such as photosystem II, 138 cytochrome c oxidase, 139 and cytochrome bc 1 complex. 140 In the past several years, UVRR experiments have been extended to a membrane protein embedded in a synthetic lipid bilayer. 141,142 In particular, UVRR studies of outer membrane protein A (OmpA) and its mutants revealed tryptophan–lipid interactions during the insertion and folding of OmpA into bilayers of small unilamellar vesicles.…”
Section: Ultraviolet Resonance Raman (Uvrr) Spectroscopymentioning
confidence: 99%
“…54 Through resonance enhancement, UV probe wavelengths select for contributions from aromatic species in proteins. 55,56 These species include tyrosine and tryptophan and their corresponding radicals {for recent examples, see 5761 }. To avoid UV damage, a flowing sample is employed.…”
Section: Overview Of Uv Resonance Raman Spectroscopymentioning
confidence: 99%